2022
DOI: 10.1038/s41420-022-01099-x
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine (m6A) methyltransferase METTL3 regulates sepsis-induced myocardial injury through IGF2BP1/HDAC4 dependent manner

Abstract: Recent studies have identified that N6-methyladenosine (m6A) extensively participates in the myocardial injury pathophysiological process. However, the role of m6A on sepsis-induced myocardial injury is still unclear. Here, we investigated the functions and mechanism of m6A methyltransferase METTL3 for septic myocardial injury. Results illustrated that the m6A modification level and METTL3 up-regulated in the lipopolysaccharide (LPS)-induced cardiomyocytes (H9C2 cells). Methylated RNA immunoprecipitation seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…In recent years, it has been gradually recognised that ferroptosis correlates with the occurrence and progression of various diseases, including ALI 21 . m6A modification has recently attracted attention because of its vital role in gene expression regulation 22–25 . In our previous study, we identified that m6A levels are significantly upregulated in NET‐treated alveolar epithelial cells in vitro and by modulating METTL3 expression through knockdown or overexpression in alveolar epithelial cells, we demonstrated that METTL3 is a crucial contributor to m6A levels 16,26 .…”
Section: Introductionmentioning
confidence: 67%
“…In recent years, it has been gradually recognised that ferroptosis correlates with the occurrence and progression of various diseases, including ALI 21 . m6A modification has recently attracted attention because of its vital role in gene expression regulation 22–25 . In our previous study, we identified that m6A levels are significantly upregulated in NET‐treated alveolar epithelial cells in vitro and by modulating METTL3 expression through knockdown or overexpression in alveolar epithelial cells, we demonstrated that METTL3 is a crucial contributor to m6A levels 16,26 .…”
Section: Introductionmentioning
confidence: 67%
“…The pathophysiological mechanism of sepsis-induced myocardial injury is complex, involving both pathogens and the host immune system. It has also been demonstrated that m 6 A methylation plays a significant regulatory role in sepsis-induced myocardial injury ( 24 ). Shen et al.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the roles in neoplastic diseases, IGF2BP1 is also involved in several nonneoplastic conditions. For example, the role of the METTL3/IGF2BP1/HDAC4 axis was illustrated in sepsis-associated myocardial injury, providing a novel therapeutic strategy 73 . In this study, we found high IGF2BP1 expression in septic AKI and that the level of IGF2BP1 was positively correlated with pyroptosis in renal tubular cells.…”
Section: Discussionmentioning
confidence: 99%